The Influence Of Creative Projects Through Entrepreneurship Education On Entrepreneurial Motivation In Vocational High School Students: A Systematic Literature Review - Sugihartono, Agus; Indah K, Luluk Nur; Wati, Andi Prasetyo; Murwani, Fulgentius Danardana; Wardana, Ludi Wishnu (PT. EQUATOR SINAR AKADEMIA, 2024)
The development of Vocational School Creative and Entrepreneurship Projects (PKK) is expected to produce graduates who can produce products and services that are needed by society while also having economic value. Therefore, PKK learning in vocational schools has an important role in preparing graduates to be ready to enter the world of work through entrepreneurship as well as being a preferred path to employment. The (SLR) method is used to compile this scientific article. About research methods: